Using Leaves as a Model for Teaching Watershed Concepts in Natural Resources Science and Engineering Programs - Anandhi, Aavudai; Yang, Yang; Hubenthal, Michael (My University, 2018)
Core Ideas Watershed is an important concept in science and engineering of natural resources. Introducing watershed concept using a leaf that students see every day is novel. Using leaf analogy, watershed concept can be taught universally. This article examines the effects of using leaves, something most students see every day and have some familiarity with, as an analogy for the concept of watersheds in an undergraduate water resources engineering course. The ultimate goal of the leaf/watershed analogy and associated instruction is to increase students’ understanding of hydrology principles, which in turn may facilitate better watershed management through increased public awareness, increased adoption of appropriate best management practices, and improved policy decisions. The assessment was performed with junior and senior undergraduate students enrolled in a Water Resource Engineering course. The assessment results showed that overall, students benefitted from the leaf analogy as a tool for learning watersheds. However, this effect varied depending on students’ learning style preferences.